1990
DOI: 10.1093/ajcn/52.6.1087
|View full text |Cite
|
Sign up to set email alerts
|

Iodine and selenium deficiency associated with cretinism in northern Zaire

Abstract: Selenium status was determined in an endemic-goiter area and in a control area of Zaire. Compared with the reference values of a noniodine-deficient area, serum selenium in subjects living in the core of the northern Zaire endemic-goiter belt (Karawa villages) was seven times lower in 52 school-children and similarly low in 23 cretins; erythrocyte glutathione peroxidase (RBC-GPX) was five times lower in schoolchildren and still two times lower in cretins (P = 0.004). In a less severely iodine-deficient city of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 13 publications
1
120
1
3
Order By: Relevance
“…Low RBC-GPX was associated with increased TSH levels. They concluded that combined iodine and Se de®ciency may be associated with the elevated frequency of endemic myxoedematous cretinism in Central Africa (Vanderpas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low RBC-GPX was associated with increased TSH levels. They concluded that combined iodine and Se de®ciency may be associated with the elevated frequency of endemic myxoedematous cretinism in Central Africa (Vanderpas et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, Se de®ciency can lower deiodinase activity and adversely affect thyroid metabolism (Beech et al, 1995;Beckett et al, 1991). In humans, cross-sectional studies have suggested that poor Se nutrition may be associated with impaired thyroid metabolism in iodine-de®cient populations (Vanderpas et al, 1990;Thilly et al, 1993). There are no published data describing the use of oral iodized oil to treat iodine de®ciency in children who are both iodine and Se de®cient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 A combination of Se and iodine deficiency exacerbates hypothyroidism and may manifest itself as myxoedematous cretinism, such as is seen in the Democratic Republic of Congo (Zaire) where deficiencies of both these minerals exist. 46 Cardiovascular Disease There is some evidence to suggest that selenium may be protective against cardiovascular disease. 4 On theoretical grounds, this is supported by the ability of GPx to combat the oxidative modification of lipids and to reduce platelet aggregation.…”
Section: Thyroid Functionmentioning
confidence: 99%
“…Akbaraly et al (77) RCT have found that Se supplementation tends to reduce mortality Bjelakovic et al (78) Thyroid effects The iodothyronine deiodinases that produce the active form of thyroid hormone are selenoenzymes, while the antioxidant selenoenzyme GPx is required for the protection of the thyroid from the H 2 O 2 produced there Arthur & Beckett (79) Severe Se deficiency occurs in the endemic goitre belt of north Zaire, which together with iodine deficiency gives rise to myxoedematous cretinism Vanderpas et al (80) An inverse association has been found between Se status and thyroid volume, thyroid tissue damage and goitre in French women Derumeaux et al (81) In RCT in patients with thyroid peroxidase antibodies or autoimmune thyroiditis Se supplementation decreases inflammation and thyroid antibody concentrations and prevents postpartum hypothyroidism Summarised in Rayman (9) GPx, glutathione peroxidise; NHANES III, Third National Health and Nutrition Examination Survey; RCT, randomised controlled trials.…”
Section: Antiviral Effects and Hivmentioning
confidence: 99%